2014
DOI: 10.1175/jcli-d-13-00384.1
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Estimated Global Water Cycle Variations over the Satellite Era

Abstract: Motivated by the question of whether recent interannual to decadal climate variability and a possible “climate shift” may have affected the global water balance, we examine precipitation minus evaporation (P – E) variability integrated over the global oceans and global land for the period 1979–2010 from three points of view—remotely sensed retrievals and syntheses over the oceans, reanalysis vertically integrated moisture flux convergence (VMFC) over land, and land surface models (LSMs) forced with observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 92 publications
(106 reference statements)
0
31
0
Order By: Relevance
“…For some time, it will be difficult to determine with certainty which changes are part of a real, long-term trend and which are related to interdecadal natural variability, but that should not discourage the effort. The analysis of Robertson et al (2014) is a step in that direction. Third, as old satellites are decommissioned and new ones are launched, it will be important to identify ensuing discontinuities in the data record (see, e.g., T11).…”
Section: E Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For some time, it will be difficult to determine with certainty which changes are part of a real, long-term trend and which are related to interdecadal natural variability, but that should not discourage the effort. The analysis of Robertson et al (2014) is a step in that direction. Third, as old satellites are decommissioned and new ones are launched, it will be important to identify ensuing discontinuities in the data record (see, e.g., T11).…”
Section: E Future Directionsmentioning
confidence: 99%
“…Sparse ground-based data and simple water budget analyses were used to estimate spatial patterns of precipitation and evapotranspiration respectively. Because long-term measurements of river discharge are also limited in availability (Alsdorf et al 2007), it is generally estimated as the difference of precipitation minus evapotranspiration in the above-mentioned studies (despite significant uncertainty therein; see Robertson et al 2014), based on assumptions of negligible long-term net water storage change, or by using a model to account for storage changes. Given current capabilities to observe terrestrial water storage changes using the NASA and German Gravity Recovery and Climate Experiment (GRACE) mission (Tapley et al 2004;Wahr et al 2004), the storage term can now be quantified with confidence in water budget analyses (Rodell et al 2004a;Syed et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The version used in this study is an update of the version previously published (Yu and Weller 2007). Studies have shown that the combined E 2 P from OAFlux and GPCP produces a freshwater budget that is best consistent with the ocean salt content (Schanze et al 2010;Ren et al 2014) and the atmospheric moisture content (Robertson et al 2014) among the products chosen for evaluation. The authors in this study are aware of several other satellite-based E and P products.…”
Section: B Satellite E 2 P Productsmentioning
confidence: 99%
“…However, differences between GPCP and CMAP over the ocean are noted, particularly in the tropical and high latitudes (Yin et al 2004). These differences are attributed largely to the inclusion of in situ rain gauge measurements and to the technical limitations in retrieving snowfall and coldseason P. To overcome the uncertainties associated with satellite P products, dynamically based metrics, such as the atmospheric conservation of moisture, are introduced to relate E 2 P to vertically integrated moisture convergence (Trenberth et al 2011;Robertson et al 2014). This type of approach is deemed more reliable, as it allows the fidelity of E 2 P produced by model physics to be evaluated by analyzed state variables of wind and moisture.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade or more, efforts have moved from sensor-specific approaches to an emphasis on intercalibration and algorithms that can provide consistent time series of geophysical constituents from multiple satellite sensors [Berg et al, 2013;Robertson et al, 2014;Hou et al, 2014]. The approach detailed here follows previous studies that iteratively solve for geophysical parameters by forward modeling the atmosphere and finding a solution that closely matches observed radiances, balancing observations with prior knowledge of the state vector [Deblonde and English, 2003;Bettenhausen et al, 2006;Boukabara et al, 2011;Munchak et al, 2016;EK08].…”
Section: Introductionmentioning
confidence: 99%